Critical Review: Secondary School Climate and Adolescents' Emotional Well-Being - Sandra Bosacki; Victoria Talwar; Serena Lecce (MDPI AG, 2023)
The social and emotional health of adolescents is increasingly a concern worldwide. To date, there remains a lack of research on how school climate influences adolescents' learning experiences and their social and emotional health. To address this gap in the literature, this critical review addresses the role that the school climate plays in an adolescent's school life and emotional well-being. This article takes a critical approach and outlines the key issues in research on the secondary school climate in the digital and real-life sense and the implications for adolescent's well-being. We first outline the definitional and methodological issues regarding research on school climate in adolescence. We then outline why mental health is a key issue for adolescents across the globe and conclude with a list of implications for theory, research, and practice. Thus, this article builds on past, current, and ongoing research on adolescents' emotional well-being and school climate across the globe. The article provides new directions and recommendations for future research on inclusive educational philosophies and positive psychology and suggestions for practice aimed to best support adolescents' learning experience and mental well-being.